Habitat occupancy of sloth bear Melursus ursinus in Chitwan National Park, Nepal. Issue 3 (6th March 2022) - Paudel, Rajan Prasad; Kadariya, Rabin; Lamichhane, Babu Ram; Subedi, Naresh; Sashika, Mariko; Shimozuru, Michito; Tsubota, Toshio
Abstract: Mammals have experienced a massive decline in their populations and geographic ranges worldwide. The sloth bear, Melursus ursinus (Shaw, 1791), is one of many species facing conservation threats. Despite being endangered in Nepal, decades of inattention to the situation have hindered their conservation and management. We assessed the distribution and patterns of habitat use by sloth bears in Chitwan National Park (CNP), Nepal. We conducted sign surveys from March to June, 2020, in 4 × 4 km grids ( n = 45). We collected detection/non‐detection data along a 4‐km trail that was divided into 20 continuous segments of 200 m each. We obtained environmental, ecological, and anthropogenic covariates to understand determinants of sloth bear habitat occupancy. The data were analyzed using the single‐species single‐season occupancy method, with a spatially correlated detection. Using repeated observations, these models accounted for the imperfect detectability of the species to provide robust estimates of habitat occupancy. The model‐averaged occupancy estimate for the sloth bear was 69% and the detection probability was 0.25. The probability of habitat occupancy by sloth bears increased with the presence of termites and fruits and in rugged, dry, open, undisturbed habitats. Our results indicate that the sloth bear is elusive, functionally unique, and widespread in CNP. Future conservation interventions and action plans aimed at sloth bear management must adequately consider their habitat requirements. Abstract : The current distribution and determinants of habitat use by the sloth bear in a protected area from Nepal are clarified using an occupancy method.